A Conceptual and Textual Analysis of Israf (Excessiveness) in The Qur’an and The New Testament - Abdelgalil, Reda (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
The article explores the multifaceted concept of israf (excessiveness) within the Qur’an and the New Testament. Using an analytical approach, it examines the connotations and implications of israf in religious, moral, and social contexts. A comparative method is also employed to identify similarities and differences in how israf is conceptualized within the scriptures of Christianity and Islam. The study emphasizes fostering a balanced and moderate outlook on life, promoting sustainable use of natural resources, and nurturing harmonious human relationships free from transgression, oppression, and violations of divine laws. It provides academic insights into both scriptures shared religious, ethical, and social foundations, highlighting the adverse consequences of israf in its various forms. The findings underscore the role of the Qur’an and the New Testament in advocating moderation across different aspects of human life, contributing to the development of a virtuous and humane society in contemporary contexts